O impacto da dimensão da firma de auditoria no custo da dívida de pequenas empresas portuguesas com auditoria voluntária - Pais, C. A. F. (2019 14th Iberian Conference on Information Systems and Technologies (CISTI), 2019)
For specific Portuguese small companies is not mandatory to have their financial statements audited. Measuring the audit quality by the dimension of the audit firm, I analyse the impact of voluntary audit by Big 4 firms on the cost of debt of Portuguese small companies. I find evidence, that it cannot be concluded that the audit quality measured by the dimension of the audit firm influences the cost of debt of the voluntary audited companies. This may be due to the fact that on small firms, the quality differences between large and small audit firms decreased when the risk of litigation is weak and therefore what matter is the audit and not the auditor.